Small animal disease surveillance: pruritus, and coagulase‐positive staphylococci. (8th October 2016) - Sánchez‐Vizcaíno, Fernando; Singleton, David; Jones, Philip H.; Heayns, Bethaney; Wardeh, Maya; Radford, Alan D.; Schmidt, Vanessa; Dawson, Susan; Noble, Peter J. M.; Everitt, Sally
Abstract : Presentation for pruritus comprised 6.5 per cent, 3.6 per cent and 2.0 per cent of canine, feline and rabbit consultations, respectively, between January 2014 and June 2016 Topical antimicrobials were the most commonly prescribed pruritus treatments for dogs (33.6 per cent of consultations); for cats, it was systemic glucocorticoids (53.5 per cent) In surveillance of coagulase‐positive staphylococci, 16 per cent of 176 coagulase‐positive staphylococci isolated from canine diagnostic samples were sensitive to all tested antibacterial classes; multidrug resistance (resistance to three or more antibacterial classes) was found in 6.8 per cent